16S rDNA-based analysis reveals cosmopolitan occurrence but limited diversity of two cyanobacterial lineages with contrasted patterns of intracellular carbonate mineralization - Ragon, Marie; Benzerara, Karim; Moreira, David; Tavera, Rosaluz; López-García, Purificación (Frontiers in Microbiology, 2014)
Cyanobacteria are mainly thought to induce carbonate precipitation extracellularly via their photosynthetic activity combined with the nucleation potential of exopolymeric substances. The discovery in microbialites of the alkaline lake Alchichica (Mexico) of Candidatus Gloeomargarita lithophora, a cyanobacterium forming large amounts of intracellular Mg-Ca-Sr-Ba carbonate spherules, showed that intracellular biomineralization in cyanobacteria is also possible. A second cyanobacterium isolated from the same environment, Candidatus Synechococcus calcipolaris G9, has been recently shown to also form intracellular calcium carbonates at the cell poles, a capability shared by all cultured species of the Thermosynechococcus clade, to which it belongs. To explore the diversity of these two distant cyanobacterial lineages representing two different patterns of intracellular calcification, we designed specific primers against their 16S rRNA genes and looked for their occurrence in a wide variety of samples. We identified the presence of members of the Gloeomargarita and Thermosynechococcus/S. calcipolaris lineages in microbialites collected from Lake Alchichica and three other neighboring Mexican lakes. The two clades also occurred in karstic areas and in some thermophilic or hypersaline microbial mats collected in South America and/or Southern Europe. Surprisingly, the within-group diversity in the two clades was low, especially within the S. calcipolaris clade, with all 16S rRNA gene sequences retrieved sharing more than 97% identity. This suggests that these clades are composed of a limited number of species with cosmopolitan distribution. Moreover, scanning electron microscopy coupled with energy dispersive x-ray spectrometry showed the presence of intracellularly calcifying Gloeomargarita-like cyanobacteria in fresh samples where this clade was relatively abundant, suggesting that these cyanobacteria do precipitate carbonates intracellularly under natural conditions.